Revitalization of Old Town Kulim, Kedah through a placemaking approach/ Nabilah Khairunnisha Abd Samad - Abd Samad, Nabilah Khairunnisha (2019)
Malaysia is experiencing the colonization from many side. From the colonization will left a mark that will become a historic and create the identity of the place. The physical features based on the history of the places can create a strong of sense, "you are here" and peoples can flashback the history of the place .. It is should be preserve and conserve because it is an aesthetic values that will represent the historic places. The physical setting of urban design in the old town district will create a sense of belonging and sense of place that gives a strong meaning which produces certain urban activities. Nowadays, the urban modernization without considering the character and the city value cause the misidentification of the places. The historical town is basically about place-making and that can make peoples connect to the place. , this study also will show the relevant and significant of using place-making principles to reinforce the features of the historical urban identity through design spaces and also focused on the design of the streets for people to experience the town.